Comparison of two patient-based outcome measures for shoulder instability after nonoperative treatment. - Moser, J; Barker, K; Doll, H; Carr, A (2008)
This study compared the responsiveness and minimal clinically important differences of the Oxford Instability Shoulder Score (OISS) and Shoulder Rating Questionnaire (SRQ). Ninety-three patients referred to physiotherapy with shoulder instability (100 shoulders) completed the questionnaires at the initial appointment and at 1 and 9 months later. A subjective rating of change was also obtained. Both questionnaires were able to detect change (effect sizes 1.16 OISS and 0.99 SRQ). The OISS change scores correlated more consistently with patients' subjective responses. The minimal detectable change (MDC90) scores were 16% (7 points) for the OISS and 17% (8 unweighted points) for the SRQ. The minimal clinically important difference (MCID) was between 9%, 4.5 points ("slightly better" and "much better") and 13.5%, 6.5 points ("much better") for the OISS, dependent on the subjective descriptors used, and 11% (4 unweighted points) for SRQ. The MCID change scores varied in relation to the baseline level of function.